ChemInform Abstract: A K2CO3‐Mediated Regioselective Synthesis of Indole/Pyrrole‐Fused 1, 4‐Oxazines: An Unexpected Indole‐Fused Azlactone Synthesis. Issue 12 (March 2015) - Vandavasi, Jaya Kishore; Hu, Wan‐Ping; Senadi, Gopal Chandru; Boominathan, Siva Senthil Kumar; Chen, Hsing‐Yin; Wang, Jeh‐Jeng
Abstract Both terminal and internal alkynes are tolerated, but reactions with the latter are more sluggish due to increased steric hindrance.